Pengaruh Kualitas Layanan Inovasi Layanan Dan Nilai Pelanggan Terhadap Kepuasan Pelanggan Pada Travel Dulin Diluk - Ordy Valentino; Moh Agung Surianto (CERED Indonesia Institute, 2022)
This study aims to examine examine effect of service quality, service innovation, and customer value on travel dulin diluk. The information obtained from the results of this study can be used as input for further researchers and Travel Dulin Diluk. The population used for this study were all Dulin Diluk Travel customers, with a sampling technique using purposive sampling obtained a sample of 150 customers. The technique of distributing questionnaires is by distributing questionnaires through google forms to customers. The analytical model used in this study is a multiple linear regression analysis model. To determine the significance of the research variables partially to the customer, the t-test technique was used, using a significance level of 5% or 0.05. The results show that service quality has a positive and significant effect on customer satisfaction with a significance of 0.000 < 0.05, the service innovation variable has a positive and significant effect on customer satisfaction with a significance of 0.004 < 0.05 and the customer value variable has a positive and significant effect on customer satisfaction with a significance 0.006< 0.05. So the conclusion in this study is that service quality, service innovation, and customer value partially affect Dulin Diluk Travel customers